Motion Rehab AVE 3D: A VR-based exergame for post-stroke rehabilitation. (November 2017) - Trombetta, Mateus; Bazzanello Henrique, Patrícia Paula; Brum, Manoela Rogofski; Colussi, Eliane Lucia; De Marchi, Ana Carolina Bertoletti; Rieder, Rafael
Highlights: A new serious game for post-stroke rehabilitation with six different levels of exercises. This solution allows to assist the traditional therapy and motivate the patient to execute his/her rehabilitation program, under health professional supervision. A preliminary study show good results in user preferences. This approach supports first- and third-person point of views and virtual reality devices, like head-mounted displays and motion sensors. Abstract: Background and objective: Recent researches about games for post-stroke rehabilitation have been increasing, focusing in upper limb, lower limb and balance situations, and showing good experiences and results. With this in mind, this paper presents Motion Rehab AVE 3D, a serious game for post-stroke rehabilitation of patients with mild stroke. The aim is offer a new technology in order to assist the traditional therapy and motivate the patient to execute his/her rehabilitation program, under health professional supervision. Methods: The game was developed with Unity game engine, supporting Kinect motion sensing input device and display devices like Smart TV 3D and Oculus Rift. It contemplates six activities considering exercises in a tridimensional space: flexion, abduction, shoulder adduction, horizontal shoulder adduction and abduction, elbow extension, wrist extension, knee flexion, and hip flexion and abduction. Motion Rehab AVE 3D also report about hits and errors to the physiotherapist evaluate the patient's progress. Results: A pilot study with 10 healthy participants (61–75 years old) tested one of the game levels. They experienced the 3D user interface in third-person. Our initial goal was to map a basic and comfortable setup of equipment in order to adopt later. All the participants (100%) classified the interaction process as interesting and amazing for the age, presenting a good acceptance. Conclusions: Our evaluation showed that the game could be used as a useful tool to motivate the patients during rehabilitation sessions. Next step is to evaluate its effectiveness for stroke patients, in order to verify if the interface and game exercises contribute into the motor rehabilitation treatment progress.